2006
DOI: 10.1038/sj.jcbfm.9600352
|View full text |Cite
|
Sign up to set email alerts
|

Cortical δ-Opioid Receptors Potentiate K+ Homeostasis During Anoxia and Oxygen–Glucose Deprivation

Abstract: Central neurons are extremely vulnerable to hypoxic/ischemic insult, which is a major cause of neurologic morbidity and mortality as a consequence of neuronal dysfunction and death. Our recent work has shown that d-opioid receptor (DOR) is neuroprotective against hypoxic and excitotoxic stress, although the underlying mechanisms remain unclear. Because hypoxia/ischemia disrupts ionic homeostasis with an increase in extracellular K + , which plays a role in neuronal death, we asked whether DOR activation preser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
61
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 60 publications
6
61
1
Order By: Relevance
“…Early in vivo cerebral ischemia studies showed that [K + ] o could reach as high as 50 to 80 mmol/L (Somjen, 1979), and this [K + ] o increase was not linear with time but could be subdivided into three phases (Hansen, 1985). In a recent study using acute cortical slices (Chao et al, 2006) The mammalian brain can tolerate a lack of blood supply for no more than 10 mins, which is followed by an irreversible functional neuronal damage (Nedergaard and Dirnagl, 2005). In a hippocampal pyramidal neuron study, a similar time period of 8 mins was determined for reaching OGD-induced anoxic depolarization, an indication of fuel exhaustion causing ion gradient breakdown (Allen et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Early in vivo cerebral ischemia studies showed that [K + ] o could reach as high as 50 to 80 mmol/L (Somjen, 1979), and this [K + ] o increase was not linear with time but could be subdivided into three phases (Hansen, 1985). In a recent study using acute cortical slices (Chao et al, 2006) The mammalian brain can tolerate a lack of blood supply for no more than 10 mins, which is followed by an irreversible functional neuronal damage (Nedergaard and Dirnagl, 2005). In a hippocampal pyramidal neuron study, a similar time period of 8 mins was determined for reaching OGD-induced anoxic depolarization, an indication of fuel exhaustion causing ion gradient breakdown (Allen et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Coincident with the observation of a [K + ] o undershoot in the post-OGD reperfusion phase (Mü ller and Somjen, 2000;Chao et al, 2006), astrocytic V m hyperpolarized transiently on OGD withdrawal (Figure 2). Ischemia-like insults enhance cultured astrocyte Na + /K + -ATPase activity (Stanimirovic et al, 1997) suggesting a possibility that this could be a responsible mechanism for the post-OGD astrocytic V m hyperpolarization.…”
Section: Reperfusion After Oxygen and Glucose Deprivationmentioning
confidence: 99%
See 1 more Smart Citation
“…DADLE blocked PC12 cell death caused by serum deprivation in a naltrexone-sensitive manner (Borlongan et al, 2004;Su, 2000). The activation of DORs protects the cortex against anoxia-and OGD-induced alterations of potassium homeostasis (Chao et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…DORs are a class of inhibitory G protein (G i )-coupled receptor whose activation is neuroprotective against hypoxic or ischemic insults in mammalian neurons (Chao et al, 2007b;Zhang et al, 2002;Zhang et al, 2000). Recently, DORs have also been linked to HPC-mediated neuroprotective mechanisms.…”
Section: Introductionmentioning
confidence: 99%